Domoic Acid: A Review of Its Cytogenotoxicity Within the One Health Approach - Goran Gajski; Marko Gerić; Ana Baričević; Mirta Smodlaka Tanković (MDPI AG, 2024)
In this review, we toxicologically assessed the naturally occurring toxin domoic acid. We used the One Health approach because the impact of domoic acid is potentiated by climate change and water pollution on one side, and reflected in animal health, food security, human diet, and human health on the other. In a changing environment, algal blooms are more frequent. For domoic acid production, the growth of Pseudo-nitzschia diatoms is of particular interest. They produce this toxin, whose capability of accumulation and biomagnification through the food web impacts other organisms in the ecosystem. Domoic acid targets nervous system receptors inducing amnestic shellfish poisoning, among other less severe health-related problems. However, the impact of domoic acid on non-target cells is rather unknown, so we reviewed the currently available literature on cytogenetic effects on human and animal cells. The results of different studies indicate that domoic acid has the potential to induce early molecular events, such as oxidative imbalance and DNA damage, thus posing an additional threat which needs to be thoroughly addressed and monitored in the future.